Drive thru da saudade - Pinceratto, Ana Maria Perez dos Santos; Oliveira, Antônio Carlos de Jesus; Maciel, Laurinda; Santos, Cícero Ferreira dos; Freitas, Claudia Lucia de; Machado, Edileia Amorim Cordeiro; Santos, Gleiciele Avila; Silva, Luciane Pincerato da; Santos, Marly Aparecida dos; Silva, Raquel de Azevedo; Botassin, Rosa Maria Ferreira; Costa, Rosângela Cabral; et al. (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2022)
>>> ver pdf